The paradigm as a tool for critical analysis - Amadeusz Krause (Studia z Teorii Wychowania)
The article deals with the use of paradigm categories for substantive and methodological analysis of scientific texts. The author points out that scientific texts from several decades are used in pedagogy. To use them correctly, ones should have knowledge and awareness of the paradigm in which they arose. Using texts for theoretical analysis without paradigmatic awareness can lead to overinterpretation and unauthorized conclusions. The article also draws attention to the existence of publications in which their authors do not specify the paradigm in which they create their research or do it incorrectly. The ability to assess such a situation is crucial for the correct use of these studies as source materials.